1994
DOI: 10.1111/j.1365-2621.1994.tb06947.x
|View full text |Cite
|
Sign up to set email alerts
|

Assay Systems and Characterization of Pacific Whiting (Merluccius productus) Protease

Abstract: Commonly used protease assays and substrates were compared for sensitivity and simplicity in analyzing proteolytic activity in Pacific whiting causing gel weakening of surimi during heat-setting. Assay based on detection of trichloroacetic acid (TCA)-soluble products, using azocasein as substrate, showed highest sensitivity. By that assay, optimal pH of the protease was 5.5, and optimal temperature, 55°C. The validity of the assay for measuring activity was confirmed by pH profiles of residual proteolytic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 22 publications
9
111
0
2
Order By: Relevance
“…At 60 min, no protein with M r of 36, 22 and 20 kDa were found. An, Seymour, Wu and Morriessey (1994) reported that among the Pacific whiting proteins, MHC was the most extensively hydrolysed by cathepsin L, followed by troponin-T and α-and β-tropomyosin. For the control (without purified proteinase), a slight degradation of 13 myosin heavy chain was observed (lane C) (Fig.…”
Section: Myosinmentioning
confidence: 99%
“…At 60 min, no protein with M r of 36, 22 and 20 kDa were found. An, Seymour, Wu and Morriessey (1994) reported that among the Pacific whiting proteins, MHC was the most extensively hydrolysed by cathepsin L, followed by troponin-T and α-and β-tropomyosin. For the control (without purified proteinase), a slight degradation of 13 myosin heavy chain was observed (lane C) (Fig.…”
Section: Myosinmentioning
confidence: 99%
“…Alcalase was used to hydrolyse gelatin and protease activity was determined as per the method of An et al (1994). The prepared skins were mixed with distilled water at a ratio of 1:10 (w/v).…”
Section: Preparation Of Gelatin Hydrolysatementioning
confidence: 99%
“…Proteinase activity of spleen extract from each tuna was determined using casein as a substrate according to the method of An et al [31] with a slight modification. To initiate the reaction, 200 µl diluted spleen extract (500 folds) was added into assay mixtures containing 2 mg of casein, 200 µl of distilled water and 625 µl of assay buffer (0.1 M glycine-NaOH, pH 9.0).…”
Section: Enzyme Assaymentioning
confidence: 99%